2022
DOI: 10.1016/j.ajic.2021.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The safety profile of COVID-19 vaccinations in the United States

Abstract: Background/Aim Pfizer-BioNTech, Moderna, and Johnson & Johnson's Janssen are the three COVID-19 vaccines authorized for emergency use in the United States. This study aims to analyze and compare adverse events following immunization (AEFIs) associated with these COVID-19 vaccines based on Vaccine Adverse Effect Reporting System (VAERS) data. Methods We utilized VAERS data from 01 st Jan 2021 to 30 th April 2021 to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 10 publications
3
47
0
4
Order By: Relevance
“…Our odds ratio analyses confirmed that the risk of most common AEs was significantly higher in females than in males and higher after the one viral vector vaccine than after either of the two mRNA vaccines. The trends in comparative incidences of each common AE per 100,000 people following the three types of vaccines were similar to those reported in a previous study [8]. In this study, the risk of a breakthrough COVID-19 infection was higher in males than in females and higher after receiving the one viral vector vaccine than either of the two mRNA vaccines.…”
Section: Discussionsupporting
confidence: 88%
“…Our odds ratio analyses confirmed that the risk of most common AEs was significantly higher in females than in males and higher after the one viral vector vaccine than after either of the two mRNA vaccines. The trends in comparative incidences of each common AE per 100,000 people following the three types of vaccines were similar to those reported in a previous study [8]. In this study, the risk of a breakthrough COVID-19 infection was higher in males than in females and higher after receiving the one viral vector vaccine than either of the two mRNA vaccines.…”
Section: Discussionsupporting
confidence: 88%
“…Studies based on passive reporting systems report even lower incidences. Singh et al, using data covering over 230 million doses, calculated an aggregate incidence of 3 cases per million doses for mRNA-based and adenoviral vector vaccines [21]. Similarly, Almuhaid et al reported an incidence of 5.58 cases per million doses in a pooled analysis of 14 cohorts covering over 26 million doses [22].…”
Section: Discussionmentioning
confidence: 99%
“…2528 3136 ). From the search update, we identified 34 new reports across all questions (Q1=9 3745 , Q2=5 37 41 4547 , Q3=1 48 , Q4=3 39 49 50 , Q5=21 9 5170 ); we excluded five studies that only reported on combined myo- and/or pericarditis (as we located other studies with these reported separately), 7175 eight studies that did not report on confirmed cases, 7683 and three studies 8486 that did not contribute additional data to other included studies on the same cases. Tables of study characteristics, with all data on results, and risk of bias ratings for questions 1 and 2 are in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%